Empowering Migrants : Impacts of a Migrant’s Amnesty on Crime Reports - Ibáñez, Ana María (World Bank, Washington, DC, 2021)
This paper studies whether undocumented immigrants change their crime-reporting behavior after receiving a regular migratory status. It exploits a natural experiment of a massive amnesty program that gave a regular migratory status to over 281,000 undocumented Venezuelan immigrants in Colombia. The findings suggest that following the amnesty there is an increase in reporting of crimes by Venezuelan immigrants, not explained by an increase in crime overall. The results are particularly strong for reports of domestic violence and sex crimes. Results are almost entirely driven by reports by female Venezuelan immigrants, a vulnerable population, suggesting that empowerment is an important mechanism driving the behavior change.